Revealing the Subsurface Geometry of the 2023 Sumedang Earthquake Sequence Using Double-Difference Relocation and Cross-Section Analysis - Rayhan Irfan Hielmy (Journal of Computation Physics and Earth Science (JoCPES), 2025)
The Sumedang Regency experienced a significant tectonic earthquake sequence beginning on December 31, 2023, which raised concerns regarding active fault structures in the region. Identifying the precise causative fault geometry was essential for seismic hazard mitigation but remained challenging due to the complex local geology and potential location errors in preliminary data. This study investigated the source mechanism and subsurface geometry of the aftershocks recorded between December 31, 2023, and January 8, 2024. The Double-Difference (HypoDD) method was applied to relocate earthquake hypocenters by minimizing travel-time residuals, utilizing a 1-D velocity model with a variable Vp/Vs ratio. Subsequently, vertical cross-section analysis was conducted to interpret the dip patterns and fault orientation perpendicular to the seismicity trend. The results revealed a significant transformation in the spatial distribution pattern; while initial data exhibited a linear north-south trend, the relocated hypocenters formed a distinct curved cluster extending from the south toward the west. The seismic activity was concentrated at shallow depths ranging from 3 km to 17 km. Cross-section interpretations suggested two potential fault geometries: a near-vertical alignment indicating a strike-slip mechanism potentially associated with the Subang Segment of the Baribis Fault, or an inclined, slab-like structure indicative of a thrust fault system. These findings provided critical constraints for future moment tensor inversion studies.